Transverse Cervical Artery Perforator Flap: Standardized Surgical Technique and Multiple Reconstructive Opportunity in Head and Neck Surgery. Issue 6 (December 2017) - Luca, Nicola; Santana, Maria Josè; Festa, Bianca Maria; Collurà, Fabio; Righini, Stefano
Abstract : Abstract: The main purpose of head and neck reconstructive surgery is to provide anatomic restoration of the demolited region and to provide preservation and recovery of function. The anatomical investigations conducted over the years has enabled a detailed knowledge of human body vascularization, giving the opportunity to design and harvest more and more versatile and refined flaps, with increasingly satisfactory results. Even if in the last 2 decades free flaps have been considered a reconstructive criterion standard, they still determine a great physical impact for the patient and require a certain surgical experience. In particular, perforator flaps (based on vessels that, emerging from the main deep axis, supply superficial myofascial cutaneous tissues) represent the new reconstructive frontier, of which a wide variety of types has been described. Our purpose is to illustrate the preparation and harvesting of the transverse cervical artery perforator flap and the variety of its utilization in head and neck reconstruction. From February 2005 to May 2015, 41 reconstructions were performed, and not only for oncologic reasons. Thanks to its anatomical features, reduced donor site morbidity and rapid preparation, this flap is a safe and feasible alternative to most famous free and locoregional flaps. Because our outcomes in functional and aesthetic terms were mostly satisfying, we can assert that the transverse cervical artery perforator flap has an important role in an appropriate reconstructive strategy for head, neck, and oropharyngolaryngeal region.